At Heidelberg with Moudud Ahmad - Hasan, Md. Mahmudul (2021)
The impression that I formed from my Heidelberg rendezvouses with Moudud Ahmad is that the man was a true patriot and a believer in Bangladesh and in his religion. Those meetings left an incredible mark on me and increased my respect for him. I was in my early 30s at that time, and he was one of the top brass political élites of Bangladesh. His broadmindedness, self-esteem and esteem for others made it possible for him to be friendly with me and with those students at Heidelberg. His kindness and generosity struck a chord with me and have remained unforgettable.